1988
DOI: 10.1080/08964289.1988.9935120
|View full text |Cite
|
Sign up to set email alerts
|

Personality Antecedents of Burnout among Middle-Aged Physicians

Abstract: Utilizing a prospective design, this study addressed the question of whether vulnerability to burnout among physicians is associated with certain longstanding, maladaptive personality tendencies that predate entrance into medical training and subsequent exposure to the intrinsic stresses of medical practice. Subjects were 440 practicing physicians whose personality traits and psychological adjustment had been assessed with the Minnesota Multiphasic Personality Inventory (MMPI) shortly before entering medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 19 publications
4
23
0
1
Order By: Relevance
“…The study is also limited by its cross-sectional design and cannot determine causality between use of specific wellness strategies and high well-being. A number of factors, including personality [65,66,67], affect the experience of QOL and may account for some of the differences observed. Future longitudinal studies are needed to evaluate a causal relationship between physician well-being and use of specific wellness promotion strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The study is also limited by its cross-sectional design and cannot determine causality between use of specific wellness strategies and high well-being. A number of factors, including personality [65,66,67], affect the experience of QOL and may account for some of the differences observed. Future longitudinal studies are needed to evaluate a causal relationship between physician well-being and use of specific wellness promotion strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The BM has been applied to a wide variety of managerial and professional occupations in several countries including Israel (Pines et al, 1981). Moreover, it is being used in current research (e.g., McCranie and Brandsma, 1988;Pines and Guendelman, 1995;Cropanzano et al, 1997;Ito et al, 1999;Weisberg and Sagie, 1999). Is burnout, as operationalized by the BM, a one-dimensional affective state, in the sense of conceptualizing a single attribute (Lumsden, 1961), distinct from the affective states of anxiety and depression?…”
mentioning
confidence: 99%
“…Previous studies of health care workers have shown a significant negative relationship of burnout with self-esteem and active coping [27, 28]and with hardiness [29], a factor which has been found to be associated with self-esteem [30]. In fact, a logistic regression in the present study showed that, in addition to low feelings of professional fulfilment and high work load, low self-esteem, being a woman and low use of active coping were all risk factors for being in the top quartile of work-related exhaustion.…”
Section: Discussionmentioning
confidence: 99%